Fumed SiO2 nanoparticle reinforced biopolymer blend nanocomposites with high dielectric constant and low dielectric loss for flexible organic electronics. Issue 5 (14th September 2016) - Deshmukh, Kalim; Ahamed, M. Basheer; Sadasivuni, Kishor Kumar; Ponnamma, Deepalekshmi; AlMaadeed, Mariam Al‐Ali; Deshmukh, Rajendra R.; Pasha, S. K. Khadheer; Polu, Anji Reddy; Chidambaram, K.
ABSTRACT: In the present study, fumed silica (SiO2 ) nanoparticle reinforced poly(vinyl alcohol) (PVA) and poly(vinylpyrrolidone) (PVP) blend nanocomposite films were prepared via a simple solution‐blending technique. Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible spectroscopy (UV–vis), X‐ray diffraction (XRD), and scanning electron microscopy (SEM) were employed to elucidate the successful incorporation of SiO2 nanoparticles in the PVA/PVP blend matrix. A thermogravimetric analyzer was used to evaluate the thermal stability of the nanocomposites. The dielectric properties such as dielectric constant (ɛ) and dielectric loss (tan δ) of the PVA/PVP/SiO2 nanocomposite films were evaluated in the broadband frequency range of 10 −2 Hz to 20 MHz and for temperatures in the range 40–150 °C. The FTIR and UV–vis spectroscopy results implied the presence of hydrogen bonding interaction between SiO2 and the PVA/PVP blend matrix. The XRD and SEM results revealed that SiO2 nanoparticles were uniformly dispersed in the PVA/PVP blend matrix. The dielectric property analysis revealed that the dielectric constant values of the nanocomposites are higher than those of PVA/PVP blends. The maximum dielectric constant and the dielectric loss were 125 (10 −2 Hz, 150 °C) and 1.1 (10 −2 Hz, 70 °C), respectively, for PVA/PVP/SiO2 nanocomposites with 25 wt % SiO2 content. These results enable the preparation of dielectric nanocomposites using a facile solution‐casting method that exhibit the desirable dielectric performance for flexible organic electronics. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44427. Abstract :